2021
DOI: 10.1007/s41347-021-00195-6
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality Representations of Nature to Improve Well-Being amongst Older Adults: a Rapid Review

Abstract: Poor well-being amongst older adults poses a serious health concern. Simultaneously, research shows that contact with nature can improve various facets of well-being, including physical, social, and mental well-being. However, nature is not always accessible for older adults due to mobility restrictions and related care needs that come with age. A promising strategy aims at bringing nature inside through pervasive technologies. However, so far, there is little academic understanding of essential nature charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 216 publications
(130 reference statements)
0
17
0
Order By: Relevance
“…In this context, some other methods can be considered. For example, a recent effort uses virtual reality technology to deliver benefits of nature exposure for incarcerated people, which may be an option for mental healthcare in prison systems ( 56 , 63 , 64 ). Before the pandemic, a study indicated that wall-images of natural environments could make some prisoners feel calm and clear their minds ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, some other methods can be considered. For example, a recent effort uses virtual reality technology to deliver benefits of nature exposure for incarcerated people, which may be an option for mental healthcare in prison systems ( 56 , 63 , 64 ). Before the pandemic, a study indicated that wall-images of natural environments could make some prisoners feel calm and clear their minds ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Location-based technology is found as an essential element of hybrid realities, which is also understood as a key characteristic of digital placemaking (Clarke, 2021;Keegan, 2021;MacIntyre et al 2019;Witteborn, 2021). Results of the review showed that hybrid realities include location-based technology and games (Bilandzic and Johnson, 2013;Frith and Richter, 2021;Gobbo and Benedetti, 2021;Harner et al, 2017;Hjorth and Richardson, 2017;Pavlovskaya, 2016;Qabshoqa, 2018), augmented realities (Abdel-Aziz et al, 2016;Boffi, 2021;Clowater, 2021;Her, 2021;Hjorth and Richardson, 2017;Hunter et al, 2022;, immersive digital experiences (Globa et al, 2019), virtual reality (Kuchelmeister et al, 2020;Rzeszewski and Naji, 2022;van Houwelingen-Snippe et al, 2021), and digital pop-up artefacts (Fredericks et al, 2018). All of them help create realities that combine the physical and digital world with different intensitiesvirtual reality refers to a fully immersive experience in the digital environment, in contrast to digital pop-up artefacts that combine analogue and digital media for community engagement.…”
Section: Key Characteristicsmentioning
confidence: 99%
“…Nature is proposed to have a positive effect on citizens' health through increased opportunities for physical activity, greater social interaction, protection from pollutants and stress reduction (Bowler et al, 2010;Hartig et al, 2014). There is extensive empirical literature on the benefits of nature exposure for health (Bratman et al, 2019;Jimenez et al, 2021) however, the wellbeing impact of digital technology as a mediator between nature and citizens has not been fully addressed (van Houwelingen-Snippe et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the numerous benefits offered from exposure to in vivo nature, many people do not feel comfortable going into natural or "wild" environments, even if they have convenient access to them (Bixler & Floyd, 1999;Browning et al, 2017). It is important to develop and examine technologies, such as VR, that enable frequent, realistic interactions with nature, particularly in the context of older adult health promotion, given that nature may not always be accessible due to mobility restrictions and care needs related to aging, (Depledge et al, 2011;Van Houwelingen-Snippe et al, 2021). VR programs using 360-degree videos of nature are both a convenient and inexpensive way to provide access to nature (Depledge et al, 2011;Smith, 2015).…”
Section: Virtual Reality Technology Incorporating Natural Settingsmentioning
confidence: 99%